POLA PENYAKIT SANTRI DI PONDOK PESANTREN MODERN ASSALAMAH (Solidarity: Journal of Education, Society and Culture, 2013)
Modern Boarding Assalamah a modern boarding school students came from among the medium and above. The number of students in 2329 as a modern boarding school, which consists of 1,111 students sons anddaughters 1218 students. Some students are still not well behaved and still lack the awareness to health. Of unhealthy behaviors students, appear various types of diseases. The students live in dormitories provided by theboarding school, but it has exceeded the capacity of the resulting occupancy susceptible to the onset of an illness raises an issue that this study attempted to analyze the problems discussed san.